(2/3)x+9=(4/3)x-3

Simple and best practice solution for (2/3)x+9=(4/3)x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2/3)x+9=(4/3)x-3 equation:



(2/3)x+9=(4/3)x-3
We move all terms to the left:
(2/3)x+9-((4/3)x-3)=0
Domain of the equation: 3)x!=0
x!=0/1
x!=0
x∈R
Domain of the equation: 3)x-3)!=0
x!=0/1
x!=0
x∈R
We add all the numbers together, and all the variables
(+2/3)x-((+4/3)x-3)+9=0
We multiply parentheses
2x^2-((+4/3)x-3)+9=0
We multiply all the terms by the denominator
2x^2*3)x-3)-((+9*3)x-3)+4=0
We add all the numbers together, and all the variables
2x^2*3)x-3)-(27x-3)+4=0
Wy multiply elements
6x^3=0
We do not support expression: x^3

See similar equations:

| –5x+2=0 | | 9x-3x-4x-5=3x | | (8x+6)+54=180 | | 6(x/4-5=-12 | | 1+1/3x=-6 | | x-3.8=-2.1 | | 6(x/4−5)=−12 | | 8x-7+8x-20=180 | | 2x^2+9+3x=5x | | 1.1x=-44 | | x+1/3=8/3 | | 2(x+3)=3x+6-x | | 7x-(2x-8)=5x-3 | | x+2.5=-7.3 | | x-+31/4=71/2 | | 3(2m+4)=-6 | | 24x=3x+15 | | 11=2j+3 | | -x5+120=6x-1 | | 9+7b=3(b-5) | | -5w+8(w+2)=-5 | | 13a=0.065 | | 16+x=59 | | -3(5v-2)=-27-4v | | 8,7⋅h=34,8 | | 6.2/2.7=5.8/x | | c^2=15c+44 | | 3(x-1)=2(x+3 | | -0,5a+12=8 | | -3(6p-8)=40-2p | | c^2-15c=44 | | 15a=0.075= |

Equations solver categories